Associations between microstructural tissue changes, white matter hyperintensity severity, and cognitive impairment: an intravoxel incoherent motion imaging study - Lin, Huihua; Dai, Xiaomin; Su, Jiawei; Yang, Shengsheng; Zheng, Yonghong; Ma, Mingping; Yu, Shun (Frontiers in Aging Neuroscience, 2023)
Introduction: White matter hyperintensities (WMHs) are a common age-and vascular risk factor-related disease and have been recognized to play an important role in cognitive impairment. However, it is still unclear what the mechanism of this effect is. In this study, intravoxel incoherent motion imaging (IVIM) was employed to assess the microvasculature and parenchymal microstructure changes of WMHs and explore their relationship with cognitive function.: Forty-nine WMH patients and 31 healthy controls underwent IVIM imaging, a diffusion technique that provides parenchymal diffusivity D, intravascular diffusivity D*, and perfusion fraction f. The IVIM dual exponential model parameters were obtained in specific regions of interest, including deep white matter hyperintensities (DWMH), periventricular white matter hyperintensities (PWMH), and normal appearing white matter (NAWM). Independent-samples t-test or Mann-Whitney U test was utilized to compare IVIM parameters between patients and controls. The Kruskal-Wallis test or one-way analysis of variance was used to compare IVIM parameters among DWMH, PWMH, and NAWM for patients. Wilcoxon two-sample test or independent-samples t-test was used to assess the differences in IVIM parameters based on the severity of WMH. Multivariate linear regression analysis was conducted to explore the factors influencing cognitive scores. Results: WMH patients exhibited significantly higher parenchymal diffusivity D than controls in DWMH, PWMH, and NAWM (all p< 0.05). IVIM parameters in the three groups (DWMH, PWMH, NAWM) were significantly different for patients (all p＜ 0.001). The severe WMH group had significantly higher parenchymal diffusivity D (DWMH and PWMH) than mild WMH (both p ＜ 0.05). Multiple linear regression analysis identified D in DWMH and PWMH as influencing cognitive function scores (all p<0.05).Conclusion: IVIM has the potential to provide a quantitative marker of parenchymal diffusivity for assessing the severity of WMH and may serve as a quantitative marker of cognitive dysfunction in WMH patients.